(untitled) (Revista Educação, Artes e Inclusão, 2025)
When discussing dance, in all its styles, one comes to an understanding of its importance in human formation, as an educational practice. This physical activity, more than the mere reproduction of steps and movements, can present a great potential in Physical Education classes. In contribution to the vocabulary of the arts, dance can express the different alternatives of knowledge in the world, as a substantial didactic strategy in the formation of Basic Education students. In this sense, the objective of this study was to construct an educational product named “Dança, Corpo, Gestos e Movimentos Platform”, related to the teaching and appreciation of dance, which provides subsidies for Physical Education professionals in Elementary School. The study population consisted of 32 teachers working in Elementary School. For data collection, electronic questionnaires were sent distributed before the use of the electronic platform by professionals and after the work with this paradidactic material. After the analysis of the obtained data, it was found the Platform can assist teachers in preparing their classes, so that the benefits of learning related to dance are obtained in an adequate way, valuing movement and health, but also cognitive and cultural aspects.